Kotmāi læ rabīap kānl̄ưaktang samāchik Saphā ʻOngkān B̨̄orihān Sūan Tambon, Ph̨̄o. S̨̄o. 2543 (Krom Kānpokkhr̨̄ong, Krasūang Mahātthai, 1999)
Laws on elections of local administration council members.